Analysis of Convergence Actions in Efforts to Prevent and Manage Stunting in Gorontalo City - Anasiru, Mohamad Anas; Domili, Indra; Hiola, Tumartony T.; Hadi, Novian S.; Nuryani, Nuryani; Mohamad, Sinto (Jurnal Ilmiah Kesehatan (JIKA), 2024)
The government has formulated a National Strategy (STRANAS) to acceleration of stunting reduction. The prevention of stunting throughout integrated interventions (convergence actions), including nutrition-specific focused on pregnant women and children while nutrition sensitif focused on environment and sanitation. Presidential Regulation concerning the acceleration of stunting reduction is carried out holistically, integratively, and with quality carried out through coordination, synergy and synchronization. This study aims to determine the action-based convergence acceleration of the stunting reduction program and evaluate the motivational elements that influence the program's effectiveness in Gorontalo City. The study was qualitative study. The research informants were the coordinator of stunting convergence of 6 Regional Goverment Organization (RGO) level and nutritionist in the nutrition program as a key informant and regular informant as targeted group in the convergence action, health cadres and village apparatus. The study showed that stunting convergence has implemented by related RGO with 8 convergence actions including with situation analysis, activity plans, stunting crackdowns, governor regulations, human cadre development, data management systems, stunting data measurement and publication as well as annual reviews. The conclusion about the implementation of stunting convergence actions by RGO in Gorontalo City shows positive efforts to support the acceleration of stunting reduction.